SCREENING AND CHARACTERIZATION OF DEVELOPING RESISTANT CULTIVAR AGAINST ODOIPORUS LONGICOLLIS (OLIVIER) (COLEOPTERA: CURCULIONIDAE) USING REFERENCE GENOTYPES IN INDIA - Alagesan, A.; Tharani, G.; Padmanaban, B.; Vijayakumar, T. Siva; Manivannan, S. (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: The objective of the research was to develop a screening method for weevil resistance by using selected genotypes. The selected reference genotypes were screened against stem weevil to deals with the different parts in India. Methods: The collected stem pieces of each cultivar were cut into 30 cm length and kept in an insect breeding chamber for two polypropylene cages is one into another. The bottom of the inner cage is made holes to drain the water from stem discs and the outer cage is without holes to collect it. Reproductively active and healthy weevils (4 females and 4 males) were selected and released into the breeding chamber for each commercial cultivar and screened against Odoiporus longicollis and observation was taken after 38 d. Based on the following method, different states of insect cultures were screened under in vitro conditions. This experiment was replicated four times for further statistical analysis. Results: The resistant genotype had significantly more (p<0.05) mortality, and fewer than the susceptible genotypes. These results indicated that the genotypes can be used as reference genotypes in evaluating resistance or susceptibility against the banana stem weevil using Gas chromatography with antennogram detector. This implies that the infestation caused by the weevils varied in different genotypes and also this information will be further helpful in selecting the resistant cultivars for future in the field of Agriculture. Conclusion: In commercial cultivars, no one can report the divergent and screening of stem weevil under in vitro conditions. In field conditions, that are not accuracy because, Climate change, Adaptation of host, migration and etc. For this instance, we performed the in vitro screening study and it finally revealed the susceptible and resistant genotypes based on the percent of weevil infestation are the same as well as no significant differences between different banana growing areas in India. Keywords: Banana stem weevil (Odoiporus longicollis), Screening, Host-plant resistance, Resistant genotypes, Biodiversity, Gas chromatography with Electroantennogram detector (GC-EAD)